«It’s better if you’re a tomboy»: construction of gender identity in the performance of female k-pop cover artists from Lima - Saavedra Echenique, Cristina (2022)
K-pop cover groups in Lima aim to emulate Korean artists, both aesthetically and artistically, through strict formulas and structures. One type of cover is the tomboy, a group composed exclusively of young women who play male artists, from the haircut to the way they move on stage. In an effort to carry out the most exact performance possible, the members of tomboy cover groups develop a corporal and attitudinal visuality that breaks social rules, especially gender ones, and above all when it goes beyond the stages and territories of the urban tribe of k-popers, that is, when extrapolated to everyday life. Confrontation does not seem to be the primary objective of these young women, but, deliberately or not, this performance represents a way of building a gender identity dissimilar to the social construct.